A giant choledochal cyst in infancy: a case report - Nursel Yurttutan; Suleyman Cuneyt Karakus; Naim Koku; Mustafa Demirci; Ramazan Ucak (Korean Pediatric Society, 2016)
Choledochal cyst is a dilation that encloses the intrahepatic or both extra- and intrahepatic portions of the biliary ducts. Postnatally, ultrasonography is the initial diagnostic modality of choice, allowing for precise measurements of intra- or extrahepatic duct dilatation and identification of stones and sludge. Symptoms depend on the age at presentation. Common bile duct malformations should be considered as a differential diagnosis of a cystic mass regardless of the cyst's size or patient's age, especially in children presenting with abdominal pain, jaundice, and palpable mass. To the best of our knowledge, we report the largest choledochal cyst in infancy.